2014
DOI: 10.1038/onc.2014.400
|View full text |Cite
|
Sign up to set email alerts
|

LincRNA-uc002yug.2 involves in alternative splicing of RUNX1 and serves as a predictor for esophageal cancer and prognosis

Abstract: Long intergenic noncoding RNAs (lincRNAs) have critical regulatory roles in cancer biology; however, the contributions of lincRNAs to esophageal squamous cell carcinoma (ESCC) have been infrequently explored. The aim of this study was to explore the contribution of lincRNAs, located at ESCC susceptibility loci identified by genome-wide association studies, to the risk and prognosis of ESCC. The associations between lincRNAs and the risk and prognosis of ESCC were analyzed in 358 diagnosed patients from eastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 46 publications
2
49
0
Order By: Relevance
“…The possibility that other mechanisms are involved also needs to be considered. 18 Pathogenic functions of RUNX1a have been reported in mouse models. However, this is not clear in patients with myeloid neoplasms.…”
Section: Resultsmentioning
confidence: 99%
“…The possibility that other mechanisms are involved also needs to be considered. 18 Pathogenic functions of RUNX1a have been reported in mouse models. However, this is not clear in patients with myeloid neoplasms.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that lncRNAs play crucial roles in the occurrence and development of ESCC (Wu et al , ; Yao et al , ; Zhang et al , ). In our study, the most notable finding was that the noncoding function of NELFA mRNA plays an important role in oesophageal cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA uc002yug.2 was overexpressed in esophageal cancer, which could exert oncogenic effect by overexpressing RUNX1a and reducing CEBPα gene expression. These data suggest that lincRNA-uc002yug.2 level could be a prognostic factor for the esophageal cancer patients’ survival [58]. …”
Section: Potential Biomarkers and Therapeutic Targets For Human Esophmentioning
confidence: 99%